Electricity costs for grinding of cement with expanding additives - Samchenko, Svetlana; Zorin, Dmitriy (International Journal of Engineering and Technology, 2018)
The most popular building material, including on transport facilities, is cement. Cement production is associated with the electricity costs. The biggest cost item is the consumption for the cement clinker grinding. It is known that disperse characteristics of cements, such as fineness of grinding, specific surface, coarseness of grading, largely determine their hydraulic properties, and for expanding cements - the deformation ones. In the paper, the issues of electric power consumption were considered when grinding extender expanders: aluminous slag, sulfoaluminate, sulfoferrite and sulfoalumoferrite clinkers.Â Â